PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ADOBE FLASH CS3 PROFESSIONAL PADA MATERI PENYAJIAN DATA - Savitri Septiara Pratiwi; Ana Setiani; Novi Andri Nurcahyono (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2019)
The purpose of this research are : 1) knowing the process of developing interactive with using Adobe Flash CS3 Professional media, 2) knowing the effectiveness of interactive learning with using Adobe Flash CS3 Professional media, 3). knowing the ability of students' mathematical understanding after using the Adobe Flash CS3 Professional media. The type of research is Research and Development (R & D) with One-Group Pretest-Posttest. The research was conducted at Mardi Waluya 2 Sukabumi Junior High School in the 2018/2019 semester event. The writer take the population of this study is on VII class. The sample used simple random sampling and for the instruments used were validation questionnaires media and tests. Data analysis techniques are using the Likert scale for validation questionnaires media, using the T test to determine effectiveness, and N-Gain to determine the increase in students' mathematical understanding skills. Interactive learning media are valued by media experts and material experts, with the results obtained that are valid so that they can be used in learning. The results of the effectiveness test are Thit (8.78)> T table (1,699) with a significant level used which is 5%. With high criteria of N-Gain test results are 75.61. Based on the results of these studies, interactive learning with using Adobe Flash CS3 Professional media can be effective in learning and can improve students' of mathematical understanding skills.